TREATMENT OF THE HUMAN BODY WITH NATURAL PRODUCTS RICH IN BIOMINERALS - Askarov Ibragim Rakhmonovich; Karimov Islambek Jumaboy o’g’li (American Journals Publishing, 2023)
Today, it is well known that the disease of every organ and tissue is caused by a cold. Inflammation (inflammation) includes all types of acute bacterial and viral diseases. This article provides information on the study of the amount of bioelements in a person with a cold and treatment with natural products.
Keywords: cold, therapy, bioelement, fluid, blood plasma, erythrocyte, urine.